Blood biochemistry and haematology of migrating loggerhead turtles (Caretta caretta) in the Northwest Atlantic: reference intervals and intra-population comparisons. Issue 1 (7th February 2019) - Yang, Tiffany; Haas, Heather L; Patel, Samir; Smolowitz, Ronald; James, Michael C; Williard, Amanda S
Abstract : We established reference intervals for blood biochemistry and haematology of loggerhead turtles captured off the Mid-Atlantic coast of the USA. This assessment of blood variables in healthy, wild loggerhead turtles allows for comparisons with turtles impacted by anthropogenic and environmental threats, as well as turtles sampled in different habitats and life stages. Abstract: We documented blood biochemistry and haematology of healthy loggerhead turtles ( Caretta caretta ) in the Northwest (NW) Atlantic in order to establish clinical reference intervals (RIs) for this threatened population. Blood samples were analysed from migratory loggerheads captured off the Mid-Atlantic coast of the USA in 2011, 2012, 2013 and 2016 as part of a long-term research program. Blood variables were determined using a point-of-care analyser, and a veterinary diagnostic laboratory service. We calculated 95% RIs with associated 90% confidence intervals (CIs) for each blood variable. We compared results obtained from our study of migratory loggerheads with published data for similarly sized loggerheads resident at a seasonal temperate latitude foraging area. Significant differences in several blood variables between migratory and resident turtles provided insight on energetic and health status during different behavioural states. Temperature was significantly correlated with several blood variables: lactate, pCO2, sodium, haemoglobin and lactate dehydrogenase. Our assessment of blood chemistry in healthy loggerhead turtles in the NW Atlantic provides a baseline for clinical comparisons with turtles impacted by anthropogenic and environmental threats, and highlights the importance of identifying unique aspects of biochemical and haematological profiles for sea turtles at the intra-population level.